2012
DOI: 10.3389/fphys.2012.00024
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotectant Ursodeoxycholyl Lysophosphatidylethanolamide Increasing Phosphatidylcholine Levels as a Potential Therapy of Acute Liver Injury

Abstract: It has been long known that hepatic synthesis of phosphatidylcholine (PC) is depressed during acute such as carbon tetrachloride-induced liver injury. Anti-hepatotoxic properties of PC as liposomes have been recognized for treatment of acute liver damage. Ursodeoxycholate (UDCA) is a known hepatoprotectant in stabilizing cellular membrane. For therapeutic management of liver injury, we coupled UDCA with a phospholipid known as ursodeoxycholyl lysophosphatidylethanolamide (UDCA-LPE). UDCA-LPE has been shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
1
9
0
1
Order By: Relevance
“…Moreover, as discussed above, the competition of UDCA‐LPE with PC may also induce the displacement of iPLA 2 β from the DRM‐PM‐localized fatty acid uptake complex, triggering its disintegration. The advantage of this conjugate compared with that of other iPLA 2 β inhibitors is its nontoxicity, because its breakdown products are degraded by the cellular metabolic machinery (11, 12). Thus, the development of an ingestible form of UDCA‐LPE and a validation of its clinical efficacy would offer a viable, potential treatment strategy for NASH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, as discussed above, the competition of UDCA‐LPE with PC may also induce the displacement of iPLA 2 β from the DRM‐PM‐localized fatty acid uptake complex, triggering its disintegration. The advantage of this conjugate compared with that of other iPLA 2 β inhibitors is its nontoxicity, because its breakdown products are degraded by the cellular metabolic machinery (11, 12). Thus, the development of an ingestible form of UDCA‐LPE and a validation of its clinical efficacy would offer a viable, potential treatment strategy for NASH.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse hepatocytes were isolated from 7‐ to 10‐wk‐old male wild‐type or iPLA 2 β‐null mice (kind gift from Dr. John Turk, Department of Medicine, Washington University School of Medicine, St. Louis, MO, USA) by using a 2‐step collagenase perfusion technique and purified by Percoll (17‐0891‐01; PAA, Cölbe, Germany) as described previously (12). Freshly isolated hepatocytes were plated and cultured for 16 h in M199 medium containing Hanks' salts and l ‐glutamine (E15‐838; PAA) supplemented with 1% penicillin and streptomycin (P11‐010; PAA), 100 nM dexamethasone (IO516; Sigma‐Aldrich), 0.5 nM insulin (D2915; Sigma‐Aldrich), and 4% neonatal calf serum (A15‐315; PAA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ursodeoxycholyl lysophosphatidylethanolamide (UDCA-LPE), a novel anti-inflammatory agent with hepatoprotective effects, was developed by Chamulitrat et al by coupling UDCA with a phospholipid. This drug inhibits mitochondrial damage and apoptosis, induces the survival signaling pathway, and promotes the regeneration of hepatocytes [8]. The mechanisms underlying the protective effects of this drug include shifting FA pools toward monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA), attenuating hepatofibrogenesis by impairment of TGF-β1/Smad2/3 signaling [9] and inherent, pronounced anti-inflammatory effects [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, bile acid conjugates have recently been tested such as Ursodeoxycholyl lysophosphatidylethanolamide (UDCA-LPE) that has been used on high-fat diet mouse model and showed a a modification in fatty acid metabolism, hepatoprotective and anti-inflammatory effects [103][104][105][106]. Moreover, it has been shown that UDCA-LPE modulates flawed fatty acid metabolism in mice fed High-Fat Diet (HFD) thus restoring altered lipid profiles and has pronounced anti-inflammatory effects [107].…”
Section: Cholesterol-lowering Drugsmentioning
confidence: 99%